2002
DOI: 10.3758/bf03195482
|View full text |Cite
|
Sign up to set email alerts
|

Glance analysis of driver eye movements to evaluate distraction

Abstract: With the increasing use of in-vehicle devices in cars, an understanding of the safety implications of secondary tasks has become crucial. It is now possible to study the effects of many in-vehicle devices and tasks on driving by using head-mounted eye-tracking devices (HEDs) to collect eye positions and pupil diameters, which have been considered indicators of attentional focus. The collection of eyeposition and pupil-diameter data of automobile drivers under on-road conditions and while completing various sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 11 publications
6
80
0
1
Order By: Relevance
“…Although flight simulators are widely employed for pilot training, where important decisions on crew certification are often made, there is "no substantial body of knowledge to predict or measure the effectiveness of flight training devices" (Rolfe & Hampson, 2003). Similarly, human factors research has long used on-road and simulated driving tasks to assess driver behavior and performance in the presence of a variety of technological innovations (Ben-Yaacov, Maltz, & Shinar, 2002;Brown, Tickner, & Simmonds, 1969;Decina, Gish, Staplin, & Kirchner, 1996;Landau, Laur, Hein, Srinivasan, & Jovanis, 1994;McKnight & McKnight, 1993;Nunes & Recarte, 2002;Sodhi, Reimer, & Llamazares, 2002). There are two problems with the validity of measures from many driving simulation studies.…”
Section: Simulation Validation In Past Research On Driving Behaviormentioning
confidence: 99%
“…Although flight simulators are widely employed for pilot training, where important decisions on crew certification are often made, there is "no substantial body of knowledge to predict or measure the effectiveness of flight training devices" (Rolfe & Hampson, 2003). Similarly, human factors research has long used on-road and simulated driving tasks to assess driver behavior and performance in the presence of a variety of technological innovations (Ben-Yaacov, Maltz, & Shinar, 2002;Brown, Tickner, & Simmonds, 1969;Decina, Gish, Staplin, & Kirchner, 1996;Landau, Laur, Hein, Srinivasan, & Jovanis, 1994;McKnight & McKnight, 1993;Nunes & Recarte, 2002;Sodhi, Reimer, & Llamazares, 2002). There are two problems with the validity of measures from many driving simulation studies.…”
Section: Simulation Validation In Past Research On Driving Behaviormentioning
confidence: 99%
“…In combination with the results of previous studies (Kubose et al, in press;Patten et al, 2004;Sodhi et al, 2002) With a proliferation of driver information and entertainment systems being introduced into cars, it seems that vehicle designers must be ever more careful not to distract the driver on any attentional channel. However, there is some hope for accommodating technology while maintaining performance, in the shape of multisensory displays (Lansdown, 2001, Sarter, 2000 or integrated interfaces (e.g., Michon, 1993 .…”
Section: Practical Implicationsmentioning
confidence: 63%
“…Baber, 1991, Liu, 1996. Moreover, it is possible for a dual task experiment to compete for the same resource pool without adversely affecting the primary task (Baber, 1991); conversely, some studies have found that mental secondary tasks can affect vehicle control (e.g., Patten et al, 2004, Recarte and Nunes, 2002, Sodhi et al, 2002. Furthermore, there is evidence that there are other qualitative aspects of secondary tasks which can determine the extent of their interference effects, such as whether they are forced-pace or interruptible Kersloot, 2004, Noy, Lemoine, Klachon andBurns, 2004) .…”
Section: The Debatementioning
confidence: 99%
“…There has been no research into the strategies that are used by LGV drivers to perform this task. Sodhi (2002) established that the mean 'eyes off road time' required to look at a Class III mirror (rear view mirror) in a passenger car is 0.96 seconds with a mean eye movement time of 0.32 seconds. To provide an indication of the difficulty that LGV drivers face these figures could be applied to the visual scanning of six mirrors resulting in a task time of 5.76 seconds.…”
Section: Further Researchmentioning
confidence: 99%